Primary relapse site pattern in women with triple-negative breast cancer - Beca, Francisco; Santos, Renata; Vieira, Daniella; Zeferino, Luiz; Dufloth, Rozany [UNESP]; Schmitt, Fernando (Elsevier B.V., 2014)
Despite the remarkable improvements in breast cancer (BC) characterization, accurate prediction of BC clinical behavior is often still difficult to achieve. Some studies have investigated the association between the molecular subtype, namely the basal-like BC and the pattern of relapse, however only few investigated the association between relapse pattern and immunohistochemical defined triple-negative breast cancers (TNBCs). The aim of this study was to evaluate the pattern of relapse in patients with TNBC, namely the primary distant relapse site:One-hundred twenty nine (129) invasive breast carcinomas with follow-up information were classified according to the molecular subtype using immunohistochemistry for ER, PgR and Her2. The association between TNBC and distant relapse primary site was analyzed by logistic regression. Using multivariate logistic regression analysis patients with TNBC displayed only 0.09(95% CI: 0.00-0.74; p = 0.02) the odds of, the non-TNBC patients of developing bone primary relapse. Regarding visceral and lymph-node relapse, no differences between in this cohort were found.Though classically regarded as aggressive tumors, TNBCs rarely development primary relapse in bone when compared to non-TNBC, a clinical relevant fact when investigating a metastasis of an occult or non-sampled primary BC. (C) 2014 Elsevier GmbH. All rights reserved.
Keywords: Breast cancer; Triple-negative; Recurrence; Relapse; Metastasis